Examining the Relational Models between Mysticism and Ethics according to Wainwright and their Evaluation from an Islamic Mysticism Perspective - Seyyed Ahmad Fazeli (Pizhūhish/hā-yi Falsafī- Kalāmī, 2023)
Wainwright considers the relationship between ethics and mysticism in two possible ways: 1. The destruction of ethics in the context of mysticism; 2. Strengthening ethics through mysticism. He mentioned and analyzed the reasons in each type, and then ended each section by expressing his point of view, and finally, he reached the point of view that morality and mysticism are separate from each other; In such a way that they neither strengthen each other nor destroy each other. This article, by criticizing the arguments of Professor Wainwright and enumerating and explaining the five models of the relationship between ethics and mysticism based on the perspective of Islamic mysticism, comes to the conclusion that contrary to his view, the relationship between ethics and mysticism, Those are not summarized in the two mentioned types and reducing these connections to those two types neglects many capacities involved in the discussion. With these debates, it is shown that the main arguments to prove the ineffectiveness of mysticism in forming a kind of ethics are not justified, but the arguments of the mystics in the direction that mysticism, both in the meta-ethical and in the normative stage, causes the realization of ethics, it seems sufficient. In the end, according to what has been said, we must adhere to the view that a mystical attitude is necessary for a completely ethical life (in the final stages of ethics). IntroductionThe most challenging issue under the topic of the “relationship between mysticism and ethics” is whether or not mysticism can provide the groundwork for the formation of ethics considering the view of the unity of existence. To study the relationship between ethics and mysticism, Wainwright has divided the relationships of ethics and mysticism into two parts and subsequently criticized them. In this article, we will evaluate Wainwright’s arguments and critiques and those of other experts while enumerating the typology of the relationships between mysticism and ethics to arrive at a more comprehensive view in this regard. The criticisms are presented with an Islamic mysticism approach.Examining the theories of the hindrance and weakening of ethics in mysticismBased on an argument in mysticism, apart from the Absolute Existence, other existents do not possess a genuine and true reality and they are phantasmal (vahmī). Thus, ethical matters and their laws are considered non-real matters and lose their real value. In response, it must be said that in mysticism, vahm refers to a faculty that can denote one meaning in the form of different images and thus, that multiplicities are vahmī means that they are the manifold images of a single reality.Based on another argument, in the unity of existence area, there is no possibility for an ‘other’ to be actualized as the object of a moral act as well as an independent moral agent. The answer is that what is negated in the Theory of the Personal Unity of Existence is the independent existence of manifold existents, not their actual being and manifestative distinctions.In short, the arguments concerning the weakening of ethics in mysticism indicate that mystical teachings focus a lot on individuality and the necessity of great emphasis on that is to weaken the place of the object of a moral act. It must be said in response that the main implication of such mystical teachings is a deep meaning and lofty goals and withdrawing from people, society, and similar things are not central in mysticism.Examining the theory of the independence of ethics and mysticismAfter studying and rejecting the arguments of both sides, that is, “the impossibility or weakening of ethics in the context of mysticism” and “the strengthening of ethics based on mysticism,” Wainwright concludes that they are independent of one another. The problem with his argument is that the claimed result is not produced from the aforementioned premises as well as that other main hypotheses can be raised regarding the relationship between these two sciences.Examining the theories of the strengthening or necessity of mysticism in relation to ethicsStace believes that all human beings are one in the domain of mysticism and this necessitates that the behavior of a moral agent with others is like one’s behavior with oneself and this leads to the strengthening of ethics in the context of mysticism. Wainwright raises issues against this argument and states that the characteristics of the unity of existence are not such that require oneness in the aforementioned meaning. After evaluating Wainwright’s argument, it must be said that according to Stace, the oneness of the moral agents and the object of a moral act does not refer to the oneness of the agent – while maintaining his limitations – and the other – while maintaining his limitations. Rather, it refers to the agent achieving mystical altruism in the third journey of wayfaring and in this case, Wainwright’s criticism doesn’t stand.ConclusionThe most important issue raised by Wainwright regarding mysticism and ethics was that there are two main hypotheses about the relationship between ethics and mysticism and each of them leads to false logical consequences and, as a result, ethics and mysticism are two unrelated domains. However, it is clear that neither is the deduction very logical and nor are the hypotheses regarding the relationship between ethics and mysticism limited to the instances that he has claimed; rather, five types of relations can be enumerated in this regard. It is also clear that his arguments for questioning the effectiveness of mysticism in shaping ethics are not justified; rather, the arguments of the mystics in this regard seem to be sufficient. Therefore, we must commit to the view that a mystical attitude is necessary for a fully moral life.